Co-exposure to polystyrene microplastics and lead aggravated ovarian toxicity in female mice via the PERK/eIF2α signaling pathway - Feng, Yueying; Yuan, Hongbin; Wang, Wanzhen; Xu, Yuanyuan; Zhang, Jinfeng; Xu, Hengyi; Fu, Fen (Ecotoxicology and environmental safety, 2022)
Generally, individual microplastics (MPs) or lead (Pb) exposure could initiate ovarian toxicity. However, their combined effects on the ovary and its mechanism in mammals remained unclear. Female C57BL/6 mice were used in this study to investigate the combined ovarian toxicity of polystyrene MPs (PS-MPs, 0.1 mg/d/mouse) and Pb (1 g/L) for 28 days. Results showed that co-exposure to PS-MPs and Pb increased the accumulation of Pb in ovaries, the histopathological damage in ovaries and uterus, the serum malondialdehyde levels and decreased serum superoxide dismutase and sex hormone levels significantly when compared with single PS-MPs and Pb exposure. These observations indicated that co-exposure exerted more severe toxicity to mouse ovaries and uterus. Furthermore, co-exposure to PS-MPs and Pb caused endoplasmic reticulum (ER) stress by activating the PERK/eIF2α signaling pathway in the ovary, which resulted in apoptosis. However, the oxidative and ovarian damage were alleviated, and the mRNA levels of genes related to the PERK/eIF2α signaling pathway were down-regulated to levels of the control mice in the PS-MPs and Pb co-exposed mice administered with ER stress inhibitor (Salubrinal, Sal) or the antioxidant (N-acetyl-cysteine, NAC). In conclusion, our findings suggested that the combination of PS-MPs and Pb aggravated ovarian toxicity in mice by inducing oxidative stress and activating the PERK/eIF2α signaling pathway, thereby providing a basis for future studies into the combined toxic mechanism of PS-MPs and Pb in mammals. •PS-MPs and Pb increased the accumulation of Pb in mice ovary.•PS-MPs and Pb aggravated the ovarian toxic effects of PS-MPs and Pb alone.•PS-MPs and Pb induced apoptosis via oxidative stress & activation of PERK/eIF2α.